Media Interaktif Pembelajaran Sistem Pencernaan - Daniel Runtulalu; Liliana Liliana; Kristo Radion Purba (Jurnal Infra, 2015)
The learning process can be done by utilizing multiple media, such as sounds, images, and animation. In general, the available learning media only use one medium that is either images or texts. If you only use one medium, the learning process becomes less effective. Combining some elements of these mediums will complement each other, therefore this thesis create an interactive learning media.This application have 3 menus i.e. illness, digestive system, and test. The simulation was made interactive with hover, click and drag with the mouse, and by pressing the key on the keyboard. The test menu contains multiple choice and hangman. The test menu is created so the user can remember about material that has been provided. This application was created with Adobe Flash CS6 and actionscript 3 as the programming language. Based on the results of the testing, the application can be run sufficiently and can perform all the functions. The results of the survey content, memory and subjective satisfaction has a 85% of score because of easeness of use and clear navigation. A hurried user often had difficulties in doing the test because they didn’t read the instructions given.